Preparation method of porous carbon electrode material

The comonomers containing sulfhydryl and ferrocene are prepared by using the click reaction of thioether and vinyl in the porous carbon electrode material, and polymerization is carried out on the surface of the modified MXene to form modified polyaniline/MXene, which solves the problem of insufficient circulation performance of the electrode materials made from biomass carbon and achieves efficient electrode material preparation.

CN119873815AActive Publication Date: 2025-04-25CHANGZHOU CHUANGMING CHAODIAN MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510354918.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The porous carbon electrode material made of biomass carbon has a volume effect during the ion embedding and migration process, resulting in insufficient cycling performance, limiting its application and promotion.

Method used

Through the click reaction of thioether and vinyl group and the reduction reaction of nitro group, a comonomer containing sulfhydryl and ferrocene was prepared, and polymerized on the surface of the modified MXene to form modified polyaniline/MXene, which was then coated on the surface of the porous biochar to prepare a porous carbon electrode material.

Benefits of technology

Modified polyaniline/MXene is coated on the surface of porous biochar, improving agglomeration phenomenon and oxidation resistance, improving the cycling performance and specific capacity of the electrode material, and significantly improving the oxidation resistance and cycling performance of the electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous carbon electrode material, and relates to the technical field of porous carbon electrode materials, the porous carbon electrode material is a comonomer containing thioether and ferrocene obtained through a click reaction of sulfydryl and vinyl and a reduction reaction of nitryl, the preparation method comprises the following steps: carrying out a polymerization reaction with an aniline monomer on the surface of modified MXene which is treated by a silane coupling agent and grafted with gallate to obtain modified polyaniline / MXene, and then coating porous charcoal with the modified polyaniline / MXene to obtain the porous charcoal. The porous carbon electrode material has excellent mass specific capacity, oxidation resistance and cycle performance, and is worthy of popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous carbon electrode materials, and in particular to a method for preparing a porous carbon electrode material. Background Art

[0002] Porous carbon electrode materials made from biochar have been widely studied because of their large specific capacitance, good rate performance, and low resistance. However, the electrical conductivity and electrochemical activity of biochar are relatively low, and the porous carbon electrode materials made from biochar also have a volume effect during the ion insertion and migration process, resulting in insufficient cycle performance in long-term use, which limits the application and promotion of porous carbon electrode materials made from biochar.

[0003] Previous studies have used MXene materials to improve the volume effect of carbon-based electrode materials during use. However, MXene flakes are easy to accumulate and have poor antioxidant properties. Therefore, some researchers have used polyaniline to polymerize on the MXene surface to improve the antioxidant properties of MXene and prevent flake accumulation. However, polyaniline is easy to agglomerate due to the strong force between molecular chains, so its ability to improve the antioxidant properties of MXene is limited and needs to be improved urgently.

[0004] Therefore, a suitable modification method is needed to improve the agglomeration phenomenon of polyaniline and enhance the oxidation resistance of MXene / polyaniline materials. Then, the MXene / polyaniline materials can be applied to porous carbon electrode materials to improve the cycle performance of porous carbon electrode materials, thereby obtaining porous carbon electrode materials with excellent properties such as oxidation resistance and cycle performance. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a porous carbon electrode material.

[0006] The purpose of the present invention can be achieved by the following technical solutions: A porous carbon electrode material, the preparation of which comprises the following steps: Step S1, stirring vinylferrocene, 4-nitrobenzenethiol, DMF, and 4-dimethylaminopyridine under ultraviolet light for 20-25 minutes to obtain a nitro product; adding the nitro product to toluene, heating to 45-50° C., starting reflux stirring, then adding sodium dithionite, and then reflux stirring for 1-1.5 hours to obtain a comonomer; Further, the usage ratio of vinylferrocene, 4-nitrobenzenethiol, DMF, and 4-dimethylaminopyridine is 11-12 g: 8-9 g: 160-170 mL: 0.5-0.7 g, and the power of ultraviolet light is 100-150 W; the usage ratio of nitro product, toluene, and sodium dithionite is 19-21 g: 80-90 mL: 9-10 g; During the reaction of step S1, the terminal carbon-carbon double bond of vinylferrocene and the thiol group of 2,6-bis(tert-butyl)-4-(mercaptomethyl)phenol undergo a click reaction under ultraviolet light to obtain a nitro product containing a thioether; the nitro group of the nitro product is reduced to an amino group to obtain a comonomer; Step S2: Add LiF to hydrochloric acid solution a and stir for 30-35 min, then add Ti 3 AlC 2 The powder was stirred at 40-45°C for 48-49h, and then washed with hydrochloric acid solution b and distilled water until neutral, and vacuum freeze-dried for 12-13h to obtain MXene; MXene was added to ethanol and ultrasonically dispersed for 1.5-2h, and then a silane coupling agent was added, and the reaction was stirred at 55-65°C for 18-20h to obtain NH 2 -MXene; in a protective gas atmosphere, the gallic acid ester was heated to 100-110°C under reflux stirring, and the constant temperature stirring was continued for 30-40 minutes, and then the temperature was lowered to 55-60°C and methanol and NH 2 -MXene, then add sodium methoxide and stir the reaction for 24-26 hours to obtain modified MXene; Furthermore, LiF, hydrochloric acid solution a, Ti 3 AlC 2 The dosage ratio of the powder is 3.2-3.5 g: 40-45 mL: 1.5-2 g, the concentration of the hydrochloric acid solution a is 9-9.5 mol / L, and the concentration of the hydrochloric acid solution b is 1-1.5 mol / L; the dosage ratio of MXene, ethanol, and silane coupling agent is 0.5-1.0 g: 150-160 mL: 23-24 g, and the silane coupling agent is KH550; gallic acid ester, methanol, NH 2 -MXene and sodium methoxide are used in a ratio of 19-22 g: 100-120 mL: 10-11 g: 0.2-0.3 g, and the gallic acid ester is selected from one of methyl gallate, ethyl gallate and propyl gallate; In step S2, during the reaction, MXene is prepared by chemical etching, and the surface of MXene is treated with a silane coupling agent to obtain NH 2 -MXene;NH 2 -MXene undergoes an aminolysis reaction with gallic acid ester to introduce polyphenolic hydroxyl groups into MXene to obtain modified MXene; Step S3, adding the modified MXene to the hydrochloric acid solution c, stirring for 8-10 min, adding aniline, comonomer and hexadecyltrimethylammonium bromide, stirring for 30-35 min, then dropping the hydrochloric acid solution of ammonium persulfate, stirring for 8.5-9 h in an ice bath, filtering, washing, and vacuum drying to obtain the modified polyaniline / MXene; Further, the amount ratio of modified MXene, hydrochloric acid solution c, aniline, comonomer, hexadecyltrimethylammonium bromide, and hydrochloric acid solution of ammonium persulfate is 0.3-0.35 g: 70-75 mL: 0.15-0.2 mL: 0.03-0.05 g: 0.2-0.25 g: 16-17 mL, and the concentration of hydrochloric acid solution c is 1 mol / L; the hydrochloric acid solution of ammonium persulfate is obtained by stirring and mixing 1-1.2 g of ammonium persulfate and 15-16 mL of hydrochloric acid solution c; During the reaction of step S3, under the induction of ammonium persulfate and the surface functional groups of the modified MXene and the guidance of the template agent hexadecyltrimethylammonium bromide, aniline and the comonomer polymerize on the surface of the modified MXene to obtain modified polyaniline / MXene, which can prevent the MXene sheets from re-stacking; Step S4, washing the peel, placing it in an oven at 80-85°C and drying it for 6-7h, and crushing it to obtain peel powder for later use; pre-carbonizing the peel powder at 350-360°C for 2.5-3h, and passing it through a 180-200 mesh sieve after cooling to obtain pre-carbonized peel powder; mixing the pre-carbonized peel powder, potassium hydroxide, and deionized water for 8-9h, filtering, drying at 95-100°C for 4-5h, and placing it at 500-550°C for 2-2.5h, cooling to room temperature, washing with acid solution until no bubbles are generated, filtering, washing with distilled water until neutral, and drying at 90-100°C for 10-11h to obtain porous biochar; Furthermore, the ratio of pre-carbonized peel powder, potassium hydroxide, and deionized water is 1-1.5 g: 2-3 g: 60-70 mL; the acid solution is a hydrochloric acid solution with a concentration of 1-1.5 mol / L; In step S4, during the reaction, the wood powder is activated and pore-formed with potassium hydroxide to obtain porous biochar; Step S5, adding the modified polyaniline / MXene to deionized water, ultrasonically dispersing for 30-40 minutes, and then centrifuging for 1-1.5 hours, collecting the supernatant to obtain a modified polyaniline / MXene suspension; adding the porous biochar to ethanol and ultrasonically dispersing for 35-45 minutes, and then adding the modified polyaniline / MXene suspension, stirring for 4-4.5 hours, vacuum filtering, and vacuum drying at 180-200° C. to obtain a porous carbon electrode material; Furthermore, the dosage ratio of modified polyaniline / MXene and deionized water is 1.4-1.6 g: 160-170 mL; the dosage ratio of porous biochar, ethanol, and modified polyaniline / MXene suspension is 0.1-0.2 g: 20-30 mL: 55-65 mL; the volume fraction of ethanol is 95%; During the reaction of step S5, the surface of the modified polyaniline / MXene generates hydrogen bonds with the porous biochar, thereby coating the surface of the porous biochar with the modified polyaniline / MXene to obtain a porous carbon electrode material.

[0007] Beneficial effects of the invention: The invention discloses a method for preparing a porous carbon electrode material, wherein a copolymer containing sulfide and ferrocene is obtained through a click reaction of a thiol group with a vinyl group and a reduction reaction of a nitro group, and the copolymerization monomer is polymerized with an aniline monomer on the surface of a modified MXene treated with a silane coupling agent and grafted with gallic acid ester to obtain modified polyaniline / MXene, and then the porous biochar is wrapped with the modified polyaniline / MXene to obtain a porous carbon electrode material.

[0008] The copolymer monomers introduced sulfide and ferrocene into the modified polyaniline. The ferrocene structure in the modified polyaniline molecular chain helps to promote the extension of the modified polyaniline molecular chain, which not only improves the agglomeration phenomenon of the modified polyaniline, but also improves the cycle performance of the electrode material containing the modified polyaniline. Ferrocene has good conductivity, which also helps to improve the conductivity of the polyaniline-based electrode material, thereby reducing the internal resistance of the prepared battery and improving the battery specific capacity. Coating the modified polyaniline with improved agglomeration phenomenon on the surface of the modified MXene is more conducive to avoiding the self-stacking of the modified MXene sheets. The gallic acid ester introduced in the modified MXene has polyphenolic hydroxyl groups, which has It has an excellent antioxidant effect, reduces the oxidation tendency of modified MXene, and produces a synergistic antioxidant effect with the sulfide in modified polyaniline, giving modified polyaniline / MXene excellent antioxidant properties, thereby making the porous carbon electrode material have excellent antioxidant properties; the modified polyaniline / MXene is coated on the surface of porous biochar to form modified polyaniline with improved agglomeration phenomenon and modified MXene with improved antioxidant properties and strong flexibility. The modified polyaniline / MXene also helps to improve the volume effect of polyaniline-based and porous carbon-based electrode materials during ion embedding and migration, thereby improving the cycle performance of electrode materials containing modified polyaniline.

[0009] Therefore, the porous carbon electrode material of the present invention has excellent specific capacity, oxidation resistance and cycle performance, and is worthy of popularization and use. DETAILED DESCRIPTION

[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0011] Example 1 A porous carbon electrode material, the preparation of which comprises the following steps: Step S1, stirring vinyl ferrocene, 4-nitrobenzene mercaptan, DMF, and 4-dimethylaminopyridine under ultraviolet light for 20 minutes to obtain a nitro product; adding the nitro product to toluene, heating to 45°C, turning on reflux stirring, then adding sodium dithionite, and then reflux stirring for 1 hour to obtain a comonomer; the amount ratio of vinyl ferrocene, 4-nitrobenzene mercaptan, DMF, and 4-dimethylaminopyridine is 11g:8g:160mL:0.5g, and the power of ultraviolet light is 100W; the amount ratio of nitro product, toluene, and sodium dithionite is 19g:80mL:9g; Step S2: Add LiF to hydrochloric acid solution a and stir for 30 min, then add Ti 3 AlC 2 Powder (supplier: Xinxin Technology, 200 mesh), stirred at 40 ° C for 48 hours, then washed with hydrochloric acid solution b and distilled water until neutral, vacuum freeze-dried for 12 hours to obtain MXene; MXene was added to ethanol and ultrasonically dispersed for 1.5 hours, then KH550 was added, and stirred at 55 ° C for 18 hours to obtain NH 2 -MXene; In a nitrogen atmosphere, methyl gallate was heated to 100 °C under reflux stirring, and then stirred at constant temperature for 30 min, then cooled to 55 °C and methanol and NH 2 -MXene, then add sodium methoxide and stir the reaction for 24 hours to obtain modified MXene; LiF, hydrochloric acid solution a, Ti 3 AlC 2 The dosage ratio of the powder is 3.2 g: 40 mL: 1.5 g, the concentration of hydrochloric acid solution a is 9 mol / L, and the concentration of hydrochloric acid solution b is 1 mol / L; the dosage ratio of MXene, ethanol, and KH550 is 0.5 g: 150 mL: 23 g; the dosage ratio of gallic acid ester, methanol, and NH 2 -MXene and sodium methoxide were used in a ratio of 19 g:100 mL:10 g:0.2 g; Step S3, adding the modified MXene to the hydrochloric acid solution c, stirring for 8 minutes, adding aniline, comonomer and hexadecyltrimethylammonium bromide, stirring for 30 minutes, and then dropping the hydrochloric acid solution of ammonium persulfate, stirring for 8.5 hours in an ice bath, filtering, washing, and vacuum drying to obtain modified polyaniline / MXene; the amount ratio of modified MXene, hydrochloric acid solution c, aniline, comonomer, hexadecyltrimethylammonium bromide, and hydrochloric acid solution of ammonium persulfate is 0.3g:70mL:0.15mL:0.03g:0.2g:16mL, and the concentration of hydrochloric acid solution c is 1mol / L; the hydrochloric acid solution of ammonium persulfate is obtained by stirring and mixing 1g of ammonium persulfate with 15mL of hydrochloric acid solution c; Step S4, wash the peel and place it in an oven at 80°C to dry for 6 hours, crush it to obtain peel powder for later use; pre-carbonize the peel powder at 350°C for 2.5 hours, and pass it through a 180-mesh sieve after cooling to obtain pre-carbonized peel powder; mix the pre-carbonized peel powder, potassium hydroxide, and deionized water for 8 hours, filter, dry at 95°C for 4 hours, place at 500°C for 2 hours, cool to room temperature, wash with acid solution until no bubbles are generated, filter, wash with distilled water until neutral, and dry at 90°C for 10 hours to obtain porous biochar; the amount ratio of pre-carbonized peel powder, potassium hydroxide, and deionized water is 1g:2g:60mL; the acid solution is a hydrochloric acid solution with a concentration of 1mol / L; Step S5, adding the modified polyaniline / MXene to deionized water, ultrasonically dispersing for 30 minutes, and then centrifuging for 1 hour, collecting the supernatant to obtain a modified polyaniline / MXene suspension; adding the porous biochar to ethanol and ultrasonically dispersing for 35 minutes, and then adding the modified polyaniline / MXene suspension, stirring for 4 hours, vacuum filtering and vacuum drying at 180°C to obtain a porous carbon electrode material; the amount ratio of modified polyaniline / MXene and deionized water is 1.4g:160mL; the amount ratio of porous biochar, ethanol, and modified polyaniline / MXene suspension is 0.1g:20mL:55mL; the volume fraction of ethanol is 95%.

[0012] Example 2 A porous carbon electrode material, the preparation of which comprises the following steps: Step S1, stirring vinyl ferrocene, 4-nitrobenzene mercaptan, DMF, and 4-dimethylaminopyridine under ultraviolet light for 23 minutes to obtain a nitro product; adding the nitro product to toluene, heating to 47°C, turning on reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 1.3 hours to obtain a comonomer; the amount ratio of vinyl ferrocene, 4-nitrobenzene mercaptan, DMF, and 4-dimethylaminopyridine is 11g:8g:165mL:0.6g, and the power of ultraviolet light is 100W; the amount ratio of nitro product, toluene, and sodium dithionite is 20g:85mL:9.5g; Step S2: Add LiF to hydrochloric acid solution a and stir for 33 min, then add Ti 3 AlC 2 The powder (supplier: Xinxin Technology, 200 mesh) was stirred at 43 °C for 48.5 h, then washed with hydrochloric acid solution b and distilled water until neutral, and vacuum freeze-dried for 12.5 h to obtain MXene; MXene was added to ethanol and ultrasonically dispersed for 1.7 h, then KH550 was added, and the reaction was stirred at 60 °C for 19 h to obtain NH 2-MXene; In a protective gas atmosphere, ethyl gallate was heated to 105 °C under reflux stirring, and then stirred at constant temperature for 35 min, then cooled to 57 °C and methanol and NH 2 -MXene, then add sodium methoxide and stir the reaction for 25 hours to obtain modified MXene; LiF, hydrochloric acid solution a, Ti 3 AlC 2 The dosage ratio of the powder is 3.3 g: 42 mL: 1.8 g, the concentration of hydrochloric acid solution a is 9.3 mol / L, and the concentration of hydrochloric acid solution b is 1.3 mol / L; the dosage ratio of MXene, ethanol, and KH550 is 0.7: 155 mL: 23.5 g; the dosage ratio of ethyl gallate, methanol, and NH 2 -MXene and sodium methoxide were used in a ratio of 20 g:110 mL:10.5 g:0.25 g; Step S3, adding the modified MXene to the hydrochloric acid solution c, stirring for 9 minutes, adding aniline, comonomer and hexadecyltrimethylammonium bromide, stirring for 33 minutes, and then dropping the hydrochloric acid solution of ammonium persulfate, stirring for 8.8 hours in an ice bath, filtering, washing, and vacuum drying to obtain modified polyaniline / MXene; the amount ratio of modified MXene, hydrochloric acid solution c, aniline, comonomer, hexadecyltrimethylammonium bromide, and hydrochloric acid solution of ammonium persulfate is 0.33g:73mL:0.17mL:0.04g:0.23g:16.5mL, and the concentration of hydrochloric acid solution c is 1mol / L; the hydrochloric acid solution of ammonium persulfate is obtained by stirring and mixing 1.1g of ammonium persulfate and 15.5mL of hydrochloric acid solution c; Step S4, wash the peel and place it in an oven at 83°C to dry for 6.5 hours, crush it to obtain peel powder for later use; pre-carbonize the peel powder at 355°C for 2.7 hours, cool it and pass it through a 180-mesh sieve to obtain pre-carbonized peel powder; mix the pre-carbonized peel powder, potassium hydroxide and deionized water for 8.5 hours, filter it, dry it at 95°C for 4.5 hours, place it at 530°C for 2.3 hours, cool it to room temperature, wash it with acid solution until no bubbles are generated, filter it, wash it with distilled water until it is neutral, and dry it at 95°C for 10.5 hours to obtain porous biochar; the dosage ratio of pre-carbonized peel powder, potassium hydroxide and deionized water is 1.3g:2.5g:65mL; ​​the acid solution is a hydrochloric acid solution with a concentration of 1.2mol / L; Step S5, adding the modified polyaniline / MXene to deionized water, ultrasonically dispersing for 35 minutes, and then centrifuging for 1.3 hours, collecting the supernatant to obtain a modified polyaniline / MXene suspension; adding the porous biochar to ethanol and ultrasonically dispersing for 40 minutes, and then adding the modified polyaniline / MXene suspension, stirring for 4.3 hours, vacuum filtering and vacuum drying at 190°C to obtain a porous carbon electrode material; the amount ratio of modified polyaniline / MXene and deionized water is 1.5g:165mL; ​​the amount ratio of porous biochar, ethanol, and modified polyaniline / MXene suspension is 0.15g:25mL:60mL; the volume fraction of ethanol is 95%.

[0013] Example 3 A porous carbon electrode material, the preparation of which comprises the following steps: Step S1, stirring vinyl ferrocene, 4-nitrobenzene mercaptan, DMF, and 4-dimethylaminopyridine under ultraviolet light for 25 minutes to obtain a nitro product; adding the nitro product to toluene, heating to 50° C., turning on reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 1.5 hours to obtain a comonomer; the amount ratio of vinyl ferrocene, 4-nitrobenzene mercaptan, DMF, and 4-dimethylaminopyridine is 12g:9g:170mL:0.7g, and the power of ultraviolet light is 100W; the amount ratio of nitro product, toluene, and sodium dithionite is 21g:90mL:10g; Step S2: Add LiF to hydrochloric acid solution a and stir for 35 min, then add Ti 3 AlC 2 Powder (supplier: Xinxin Technology, 200 mesh), stirred at 45 ° C for 49 hours, then washed with hydrochloric acid solution b and distilled water until neutral, vacuum freeze-dried for 13 hours to obtain MXene; MXene was added to ethanol and ultrasonically dispersed for 2 hours, then KH550 was added, and stirred at 65 ° C for 20 hours to obtain NH 2 -MXene; In a nitrogen atmosphere, propyl gallate was heated to 110 °C under reflux stirring, and then stirred at constant temperature for 40 min, then cooled to 60 °C and methanol and NH 2 -MXene, then sodium methoxide was added and stirred for 26 hours to obtain modified MXene; LiF, hydrochloric acid solution a, Ti 3 AlC 2 The dosage ratio of the powder is 3.5 g: 45 mL: 2 g, the concentration of hydrochloric acid solution a is 9.5 mol / L, and the concentration of hydrochloric acid solution b is 1.5 mol / L; the dosage ratio of MXene, ethanol, and KH550 is 1.0 g: 160 mL: 24 g; the dosage ratio of propyl gallate, methanol, and NH 2-MXene and sodium methoxide usage ratio is 22 g:120 mL:11 g:0.3 g; Step S3, adding the modified MXene to the hydrochloric acid solution c, stirring for 10 minutes, adding aniline, comonomer and hexadecyltrimethylammonium bromide, stirring for 35 minutes, and then dropping the hydrochloric acid solution of ammonium persulfate, stirring for 9 hours in an ice bath, filtering, washing, and vacuum drying to obtain modified polyaniline / MXene; the amount ratio of modified MXene, hydrochloric acid solution c, aniline, comonomer, hexadecyltrimethylammonium bromide, and hydrochloric acid solution of ammonium persulfate is 0.35g:75mL:0.2mL:0.05g:0.25g:17mL, and the concentration of hydrochloric acid solution c is 1mol / L; the hydrochloric acid solution of ammonium persulfate is obtained by stirring and mixing 1.2g of ammonium persulfate and 16mL of hydrochloric acid solution c; Step S4, wash the peel and place it in an oven at 85°C to dry for 7 hours, crush it to obtain peel powder for later use; pre-carbonize the peel powder at 360°C for 3 hours, cool it and pass it through a 180-mesh sieve to obtain pre-carbonized peel powder; mix the pre-carbonized peel powder, potassium hydroxide and deionized water for 9 hours, filter it, dry it at 100°C for 5 hours, place it at 550°C for 2.5 hours, cool it to room temperature, wash it with acid solution until no bubbles are generated, filter it, wash it with distilled water until it is neutral, and dry it at 100°C for 11 hours to obtain porous biochar; the dosage ratio of pre-carbonized peel powder, potassium hydroxide and deionized water is 1.5g:3g:70mL; the acid solution is a hydrochloric acid solution with a concentration of 1.5monl / L; Step S5, adding the modified polyaniline / MXene to deionized water, ultrasonically dispersing for 40 minutes, and then centrifuging for 1.5 hours, collecting the supernatant to obtain a modified polyaniline / MXene suspension; adding the porous biochar to ethanol and ultrasonically dispersing for 45 minutes, and then adding the modified polyaniline / MXene suspension, stirring for 4.5 hours, vacuum filtering and vacuum drying at 200°C to obtain a porous carbon electrode material; the amount ratio of modified polyaniline / MXene and deionized water is 1.6 g: 170 mL; the amount ratio of porous biochar, ethanol, and modified polyaniline / MXene suspension is 0.2 g: 30 mL: 65 mL; the volume fraction of ethanol is 95%.

[0014] Comparative Example 1 Compared with Example 3, vinylferrocene was replaced with 1-hexene, and the rest was exactly the same as Example 3 to prepare a porous carbon electrode material.

[0015] Comparative Example 2 Compared with Example 3, propyl gallate was replaced with methyl 3,5-di-tert-butyl-4-hydroxybenzoate, and the rest was exactly the same as Example 3 to prepare a porous carbon electrode material.

[0016] Comparative Example 3 Compared with Example 3, the copolymer monomer in step S3 is replaced with aniline, and the rest is exactly the same as Example 3 to prepare a porous carbon electrode material.

[0017] The porous carbon electrode material prepared by the present invention is further tested for its effect, and the test results are as follows.

[0018] The porous carbon electrode material, the conductive agent acetylene black, and the binder PTFE were mixed in a mass ratio of 8:1:1, and after adding anhydrous ethanol and stirring evenly, the mixture was heated and stirred in a 50°C water bath until it became a paste, rolled and sliced, pressed on the surface of the nickel foam, and dried for electrochemical experimental testing; the electrochemical experiment was carried out in a 6 mol / L electrolyte with a Pt mesh electrode as the counter electrode and Hg / HgO as the reference electrode, and the mass specific capacity at a current density of 0.5 A / g was recorded in Table 1, and the mass specific capacity retention rate after 10,000 cycles of charge and discharge test at a current density of 0.5 A / g was recorded in Table 1 to evaluate the cycle performance; After the porous carbon electrode material was placed in an air oven at 100°C for 7 days, the mass specific capacity retention rate after oxidation was determined by referring to the above method and recorded in Table 1 to evaluate the oxidation resistance;

[0019] According to the data in Table 1, the porous carbon electrode material of the present invention has excellent mass specific capacity, oxidation resistance and cycle performance. Comparison of Example 3 with Comparative Example 1 shows that when vinyl ferrocene is replaced with 1-hexene and ferrocene is not introduced into the modified polyaniline, the mass specific capacity of the electrode material decreases, the molecular chain extension of the modified polyaniline cannot be promoted, and the agglomeration phenomenon of the modified polyaniline cannot be improved. The cycle performance of the electrode material decreases, and the mass specific capacity retention rate of the electrode material decreases; it is also not conducive to the improvement of the conductivity of the polyaniline-based electrode material, thereby reducing the mass specific capacity of the battery. Comparison of Example 3 with Comparative Example 2 shows that the gallic acid ester is replaced with hindered phenol, and no polyphenolic hydroxyl group is introduced, so that the oxidation resistance of the modified MXene is reduced, and the synergistic oxidation resistance of the thioether in the modified polyaniline coated on the MXene is weakened, so that the modified MXene in the electrode material is reduced due to the reduced oxidation resistance, resulting in the reduced ability of the modified polyaniline / MXene to improve the volume effect of the polyaniline-based and porous carbon-based electrode materials during ion embedding and migration, thereby reducing the mass specific capacity retention rate of the porous carbon electrode material after oxidation. Comparison of Example 3 with Comparative Example 3 shows that the comonomer is replaced with aniline, and no thioether is introduced into the polyaniline, and a synergistic effect cannot be formed with the gallic acid ester in the modified MXene, and the oxidation resistance of the electrode material is reduced, and ferrocene is not introduced into the polyaniline, and the mass specific capacity of the electrode material is reduced, and the molecular chain extension of the modified polyaniline cannot be promoted, and the agglomeration phenomenon of the modified polyaniline cannot be improved, so that the cycle performance of the electrode material is reduced, and the mass specific capacity retention rate of the electrode material is reduced.

[0020] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon electrode material, characterized in that: The steps include: Step S1, stirring vinylferrocene, 4-nitrobenzenethiol, DMF, and 4-dimethylaminopyridine under ultraviolet light to obtain a nitro product; adding the nitro product to toluene, and then adding sodium dithionite, stirring and reacting to obtain a comonomer; Step S2, adding LiF to hydrochloric acid solution a, and then adding Ti3AlC2 powder, stirring and reacting to obtain MXene; adding MXene to ethanol, and then adding a silane coupling agent, stirring and reacting to obtain NH2-MXene; in a protective gas atmosphere, heating and stirring the gallic acid ester, then cooling and adding methanol, NH2-MXene and sodium methoxide, stirring and reacting to obtain modified MXene; Step S3, adding the modified MXene to the hydrochloric acid solution c, adding aniline, comonomer and hexadecyltrimethylammonium bromide, stirring, and then dropping the hydrochloric acid solution of ammonium persulfate, stirring to obtain the modified polyaniline / MXene; Step S4, washing the peel, drying it, and crushing it to obtain peel powder for later use; pre-carbonizing the peel powder and sieving it to obtain pre-carbonized peel powder; mixing the pre-carbonized peel powder, potassium hydroxide, and deionized water, and then carbonizing and post-treating it with acid to obtain porous biochar; Step S5, adding the modified polyaniline / MXene to deionized water, ultrasonically dispersing, centrifuging, and collecting the supernatant to obtain a modified polyaniline / MXene suspension; adding the porous biochar to ethanol, ultrasonically dispersing, and then adding the modified polyaniline / MXene suspension, stirring to obtain a porous carbon electrode material.

2. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S1, the usage ratio of vinylferrocene, 4-nitrobenzenethiol, DMF and 4-dimethylaminopyridine is 11-12 g: 8-9 g: 160-170 mL: 0.5-0.7 g.

3. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S1, the power of the ultraviolet light is 100-150W; the usage ratio of the nitro product, toluene and sodium dithionite is 19-21g:80-90mL:9-10g.

4. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S2, the usage ratio of LiF, hydrochloric acid solution a, and Ti3AlC2 powder is 3.2-3.5 g:40-45 mL:1.5-2 g, the concentration of hydrochloric acid solution a is 9-9.5 mol / L, and the concentration of hydrochloric acid solution b is 1-1.5 mol / L.

5. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S2, the dosage ratio of MXene, ethanol and silane coupling agent is 0.5-1.0 g: 150-160 mL: 23-24 g, and the silane coupling agent is KH550.

6. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S2, the dosage ratio of gallic acid ester, methanol, NH2-MXene and sodium methoxide is 19-22 g: 100-120 mL: 10-11 g: 0.2-0.3 g, and the gallic acid ester is selected from one of methyl gallate, ethyl gallate and propyl gallate.

7. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S3, the usage ratio of modified MXene, hydrochloric acid solution c, aniline, comonomer, hexadecyltrimethylammonium bromide, and hydrochloric acid solution of ammonium persulfate is 0.3-0.35 g: 70-75 mL: 0.15-0.2 mL: 0.03-0.05 g: 0.2-0.25 g: 16-17 mL.

8. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S3, the concentration of the hydrochloric acid solution c is 1 mol / L; the hydrochloric acid solution of ammonium persulfate is obtained by stirring and mixing 1-1.2 g of ammonium persulfate and 15-16 mL of the hydrochloric acid solution c.

9. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S4, the ratio of pre-carbonized peel powder, potassium hydroxide and deionized water is 1-1.5 g: 2-3 g: 60-70 mL; the acid solution is a hydrochloric acid solution with a concentration of 1-1.5 monl / L.

10. The method for preparing a porous carbon electrode material according to claim 1, characterized in that: In step S5, the usage ratio of modified polyaniline / MXene and deionized water is 1.4-1.6 g: 160-170 mL; the usage ratio of porous biochar, ethanol, and modified polyaniline / MXene suspension is 0.1-0.2 g: 20-30 mL: 55-65 mL; and the volume fraction of ethanol is 95%.

Citation Information

Patent Citations

  • Method for modifying elastomer by using click reaction of thiol-ene

    CN103788386A

  • Ferrocene group-containing aniline derivative polymer and use thereof

    CN104409735A

  • Aqueous zinc ion battery, polyaniline MXene / graphite felt composite positive electrode material and preparation method of polyaniline MXene / graphite felt composite positive electrode material

    CN116230896A

  • Method for improving low-temperature performance of electrode material

    CN117317150A

  • MXene modified carbon fiber non-woven felt with multi-layer structure and preparation method of MXene modified carbon fiber non-woven felt

    CN117947633A